2019
DOI: 10.1080/16070658.2019.1578115
|View full text |Cite
|
Sign up to set email alerts
|

Association of anthropometric status and residential locality factors with cognitive scores of 4–6-year-old children in Kwazulu-Natal, South Africa

Abstract: Background: The Asenze study has the long-term goal of promoting better physical, cognitive and psychosocial functioning of children in a rural area in KwaZulu-Natal, 50 km from Durban, with a view to planning interventions to promote growth and development for very young children. The specific objective in this paper was to provide information for the Child Health and Development project of the Valley Trust to assist with intervention planning. The broader goal was to assess developmental delays in communitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…While studying child cognitive and language outcomes by HIV exposure status in wave 1, Gruver et al [ 15 ] noted that for all outcome measures, HIV-exposed but uninfected children and HIV-unexposed children had comparable scores, while HIV infected children had significantly lower cognitive and language scores. Additionally, in wave 1, Ajayi et al [ 16 ] found that children with low cognitive scores were more often stunted, had no preschool education, and came from areas less favorable in terms of local infrastructure, access to employment, and arable land. Of note, it was reported that 61.2% of children had attended a crèche or preschool.…”
Section: Resultsmentioning
confidence: 99%
“…While studying child cognitive and language outcomes by HIV exposure status in wave 1, Gruver et al [ 15 ] noted that for all outcome measures, HIV-exposed but uninfected children and HIV-unexposed children had comparable scores, while HIV infected children had significantly lower cognitive and language scores. Additionally, in wave 1, Ajayi et al [ 16 ] found that children with low cognitive scores were more often stunted, had no preschool education, and came from areas less favorable in terms of local infrastructure, access to employment, and arable land. Of note, it was reported that 61.2% of children had attended a crèche or preschool.…”
Section: Resultsmentioning
confidence: 99%
“…Analyses of the first two waves of the Asenze study have shown that early health, nutrition and stimulation were important in developing cognitive skills during the preschool period [ 16 18 ]. In the present qualitative sub-study several themes emerged with respect to resilience under the crisis in the education system.…”
Section: Discussionmentioning
confidence: 99%
“…In the first wave of the Asenze assessments the cognitive development of the children was assessed using sub-studies of the KABC II, and higher scores were found not only to be associated with preschool attendance and nutritional status, but also with the area where the child lived [16][17][18]. In a path analysis of cognitive development across the first two waves nutritional status directly predicted cognitive development as measured by the KABC scores [17].…”
Section: Measures Taken From the Main Cohort Studymentioning
confidence: 99%
“…1 The difference in economy and lifestyle is significant in rural and urban areas, causing differences in nutritional status between the two. 25 The prevalence of nutrition is somewhat higher in rural than urban areas which is typical in developing countries. 23 Households in urban areas have more access to adequate sanitation and clean water as well as good parental education, thus supporting the creation of a better nutritional status.…”
Section: Introductionmentioning
confidence: 99%